Comparative Volatilomic Profiling of Beef and Pork Sausages Using HS-GCMS and Chemometric Analysis - Sandra Hermanto; Ahmad Fathoni; Barita Juliano Siregar; Denny Alfarus (UIN Sunan Gunung Djati Bandung, 2026)
Verifying the species origin of processed meat is important for both genuineness and halal compliance. This study aims to identify volatile organic compounds (VOCs) in fresh and processed meat using a volatilomic metabolomics approach. Fresh beef, fresh pork, beef sausage, and pork sausage are collected from supermarkets. For sample preparation, each meat sample was homogenized in phosphate buffer and placed in headspace vials. The VOCs were analyzed with HS-GCMS, and principal component analysis (PCA) was used to interpret the data. Fresh beef contained 50 volatile compounds, while fresh pork had 30. Beef sausage, pork sausage, and mixed beef–pork sausages (25:75 and 50:50) contained 41, 30, 38, and 50 volatile compounds, respectively. PCA results showed clear differences between beef and pork based on their chemical profiles. Hexanal and 1-octen-3-ol were strong indicators of pork, while nonanal, octanal, and benzaldehyde were typical for beef. In sausages, PC1 separated pork and beef by the types of volatile compounds from fat compared to those from protein or heme. PC2 reflected the phenolic and terpene compounds from smoke seasonings. Some VOCs, like n-hexane and N-tert-butylhydroxylamine, are commonly used in pork sausage production. The VOC profiles of mixed sausages depended on the beef-to-pork ratio. Some markers were present only in small amounts; for example, 1-octen-3-ol was detected only in the 25:75 mixture, and benzaldehyde was detected only in the 50:50 mixture. These results show that species-specific volatile compounds can still be detected in mixed sausage samples, supporting the use of volatilomics to detect adulteration.